Dip coated TiO2 based metal-semiconductor-metal ultraviolet photodetector for UV A monitoring. (May 2020) - Kumbhar, S.M.; Shevate, S.S.; Patil, A.R.; Shaikh, S.K.; Rajpure, K.Y.
Abstract: Metal-Semiconductor-Metal ultraviolet photodetector was fabricated by painting silver contacts on dip coated TiO2 thin films. The number of deposition cycles have influence on physiochemical properties and UV sensing properties. The UV photodetector properties were studied by illuminating devices with light intensity of 1.8 μW/cm 2 and 5 V bias. The fabricated devices show ohmic I–V characteristics. The maximum photocurrent of 0.64 μA is obtained at 365 nm for film deposited at 8 cycles. The highest photoresponsivity obtained for C8 sample under UV illumination of 365 nm is 2.15 A/W at 5 V bias. The fast rise and fall times obtained for fabricated device are 17 s and 19 s. The optical switching characteristics show good reproducibility and stability. Highlights: TiO2 thin film based MSM UV photodetector fabricated by dip coating method. The UV photodetectors device shows maximum photoresponse of 2.14 A/W in UV-A region. The UV photodetector shows fast optical switching with rise time and fall time of 17 sec and 19 sec respectively. The highest value of detectivity at 365nm and 5V bias is 6.01×10 12 cm. Hz 1/2 /W.